(untitled) (Santa Barbara, California, 2013)
America loves sports. This book examines and details the proof of this fascination seen throughout American society-in our literature, film, and music; our clothing and food; and the iconography of the nation.
Keywords: Sports,Athletes,Thể thao,Vận động viên; History,Lịch sử,Lịch sử; United States,United States,Hoa Kỳ